A Pilot Study: Attention Deficit Hyperactivity Disorder, Sensation Seeking, and Pubertal Changes - Catherine A. Martin; Greg Guenthner; Christopher Bingcang; W. Jackson Smith; Thomas Curry; Hatim A. Omar; Mary Kay Raynes; Thomas H. Kelly (The Scientific World Journal)
This study was designed to examine the relationship of pubertal changes and sensation seeking (SS) in adolescents with Attention Deficit Hyperactivity Disorder (ADHD). Patients with current or past histories of uncomplicated stimulant medication use for ADHD between the ages of 11 and 15 (13 ± 1.5) were recruited from a Child Psychiatry and a General Pediatric Clinic. SS was measured using the SS Scale for Children. Pubertal development was measured using Tanner staging, free testosterone, and DHEAS. Subjects and their parent were interviewed with the Diagnostic Interview Schedule for Children (DISC). SS total score was correlated with Tanner stage, free testosterone, and DHEAS (p ≤ 0.01). The combined parent and child reports of symptoms of Oppositional Defiant Disorder from the DISC were inversely related to age (p ≤ 0.05). Understanding SS in ADHD adolescents as they move through puberty will aid clinicians in monitoring ADHD adolescents and their trajectory into high-risk behaviors.